The Imperial and asiatic quarterly review and oriental and colonial record. - East India Association (London, England); Oriental Institute (Woking, England) (Oriental Institute, 1891)
Beginning Apr. 1895, includes the Proceedings of the East India Association.
Beginning in 1895, includes the Proceedings of the East India Association.
Description based on: 3rd series, vol. 33, no. 65 & 66 (Jan.-Apr. 1912)
Beginning Apr. 1895, includes the Proceedings of the East India Association.
1891-1913 published by the Oriental University Institute, Woking.
Keywords: India; Asia